What the nanny saw - Neill, Fiona (New York Riverhead Books, 2012)
When her privileged employers become the focus of a financial scandal at the height of the economic crash, a trusted nanny finds her loyalties tested by a reporter who taps her as an insider with unique perspectives into what various family members have hidden from each other.
111614
Keywords: Families -- England -- London -- Fiction; Nannies -- Fiction; Family secrets -- Fiction; Families; Family secrets; Nannies; England -- London; Domestic fiction; Fiction